Description of Bolton analysis on Balinese patients with crowded teeth in Mahasaraswati Denpasar University Dental Hospital: Gambaran analisis Bolton pada pasien dengan gigi berjejal di Rumah Sakit Gigi Mulut Universitas Mahasaraswati Denpasar - Ketut Virtika Ayu; Wiwekowati; I Gusti Putu Andya Indah Paramitha (Makassar Dental Journal, 2021)
Bolton analysis is one of the analyzes used in determining tooth size discrepancies, the ratio of size of mesiodistal teeth is very important in determining orthodontic treatment plans so that good occlusion can be achieved as a result of treatment. The aim of this study is to find out the width of mesiodistal teeth crowded with Bolton's analysis of Balinese men and women. This des-criptive research method using purposive sampling technique, used 40 models study samples of male and female from Balinese patients at the Mahasaraswati Denpasar University Dental Hospital. The largest contour of mesial to distal dimension of the tooth measured parallel to the occlusal plane. The results obtained were anterior ratios and the overall analysis of Bolton in the Balinese tribe. The anterior ratio of the Balinese men and women was obtained at 79.55%±3.40 and 61.57%±5.32. The overall ratio of Balinese men and women was obtained at 91.66%±2.57 and 102.50%±5.26. It was concluded that Bolton's anterior ra-tio and Bolton's overall ratio in crowded teeth of Balinese men and women show an average value that exceeds Bolton's ideal value, so that the location of faulty teeth of the Balinese tribe can be seen in the mandible.